2016
DOI: 10.2741/4392
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteome analysis along jejunal crypt-villus axis in piglets

Abstract: The brush-border membrane (BBM) of enterocytes is responsible for the digestion and absorption of nutrients and ions in the small intestine. To identify the BBM proteins involved in epithelial cell maturation along the crypt-villus axis, enterocytes were sequentially isolated from the villus tip to the crypt of the jejunum from 21-day-old suckling piglets. After preparation of BBM vesicles, we detected 194 proteins in the jejunal epithelial cells by isobaric tags using relative and absolute quantification (iTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The intestinal morphology plays an important role in the uptake of nutrients and the occurrence of diarrhea (Lee et al, 2013). Changes in the intestinal morphology, including villus atrophy and crypt hyperplasia, are associated with the malabsorption and growth inhibition of pigs (Xiong et al, 2016). Previous researchers have shown that a high dietary zinc treatment could improve the morphology of the small intestine (Li et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The intestinal morphology plays an important role in the uptake of nutrients and the occurrence of diarrhea (Lee et al, 2013). Changes in the intestinal morphology, including villus atrophy and crypt hyperplasia, are associated with the malabsorption and growth inhibition of pigs (Xiong et al, 2016). Previous researchers have shown that a high dietary zinc treatment could improve the morphology of the small intestine (Li et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The small intestinal epithelium is the main part that constitutes the mucosal layer, and the intestine depends mainly on the differentiation of epithelial cells to reach the intestinal barrier [ 63 ]. Researchers have demonstrated that probiotics can improve the epithelial cytoskeletal structure to maintain bacterial cell wall permeability through information transmission [ 64 ]. It has been reported that oral administration of Lacticaseibacillus rhamnosus GG (LGG) promoted the rate of weight gain in newborn mice [ 65 ].…”
Section: Probiotics Regulate Immunity Through Intestinal Floramentioning
confidence: 99%
“…Enhanced intestinal morphology and gut barrier are closely associated with nutrients absorption and intestinal integrity (42). Intestinal morphology significantly changes, including villous atrophy and crypt hyperplasia, which will result in diarrhea and growth retardation in pigs (43). An increasing VH/CD ratio is one of the most important indices of intestinal morphology in evaluating the improvement of intestinal function and enhancement of absorption capacity (44).…”
Section: Mcr Has Potential In Antioxidant and Anti-inflammation Therapy In Weaned Pigletsmentioning
confidence: 99%